2021
DOI: 10.3389/fmolb.2020.566207
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Staphylococcus aureus Associated Extracellular Vesicles Reveals Presence of Small RNA-Cargo

Abstract: Bacterial extracellular vesicles (EVs) have a vital role in bacterial pathogenesis. However, to date, the small RNA-cargo of EVs released by the opportunistic pathogen Staphylococcus aureus has not been characterized. Here, we shed light on the association of small RNAs with EVs secreted by S. aureus MSSA476 cultured in iron-depleted bacteriologic media supplemented with a subinhibitory dosage of vancomycin to mimic infection condition. Confocal microscopy analysis on intact RNase-treated EVs indicated that RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 140 publications
(164 reference statements)
2
27
0
Order By: Relevance
“…The RNA cargo of S. aureus was also recently characterized, revealing that the sRNAs RNAIII, RsaC, and SsrA (tmRNA) predominate. This suggests additional functions for these sRNAs in the control of immune host response ( Joshi et al, 2020 ; Luz et al, 2021 ), as suggested in earlier reviews ( Ellis and Kuehn, 2010 ; Avila-Calderón et al, 2015 ).…”
Section: Srna Regulation Is Required For a Variety Of Biological Functionssupporting
confidence: 67%
“…The RNA cargo of S. aureus was also recently characterized, revealing that the sRNAs RNAIII, RsaC, and SsrA (tmRNA) predominate. This suggests additional functions for these sRNAs in the control of immune host response ( Joshi et al, 2020 ; Luz et al, 2021 ), as suggested in earlier reviews ( Ellis and Kuehn, 2010 ; Avila-Calderón et al, 2015 ).…”
Section: Srna Regulation Is Required For a Variety Of Biological Functionssupporting
confidence: 67%
“…OMVs and O-IMVs are ~100 nm vesicles that subserve various functions, including pathogenpathogen interactions, and delivering virulence factors, sRNAs and tRNA fragments into host cells to modulate the host immune response (Kaparakis-Liaskos and Ferrero, 2015;Koeppen et al, 2016;Vitse and Devreese, 2020). Gram-positive bacteria and fungal pathogens also secrete EVs that contain sRNAs, tRNAs, and tRNA fragments (Peres da Silva et al, 2015;Resch et al, 2016;Alves et al, 2019;Rodriguez and Kuehn, 2020;Joshi et al, 2021). In sum, microbial EVs containing sRNAs and tRNA fragments deliver their contents to recipient cells, and a few studies have shown by transfecting synthetic RNA oligos and making sRNA-deletion mutants, that sRNAs and tRNAs regulate gene expression in eukaryotic host cells (Garcia-Silva et al, 2014a;Koeppen et al, 2016;Choi et al, 2017;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…BEVs (~20 nm to 400 nm) secreted by Gram-positive bacteria also contain sRNAs (<100 nt, with most in the range of 10 to 40 nt) [ 10 , 19 , 20 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Although recent studies have shown that sRNAs in BEVs affect host cell biology, to date no studies have identified specific sRNAs that mediate the host response to BEVs.…”
Section: Extracellular Vesicles Secreted By Bacteria Are Important Mediators Of Inter-kingdom Communication and Deliver Srna And Trna Framentioning
confidence: 99%
“…Intercellular communication mediated by EVs is an important aspect of host–pathogen interaction that does not require direct cell–cell contact, since, for example, many bacteria reside in mucus overlying epithelial cells in the gut and lungs [ 17 , 18 ]. EVs are spherical, cell-derived fragments ~10 nm to 1000 nm in diameter delimited by a lipid bilayer and contain proteins, lipids, nucleic acids and many other cellular constituents [ 2 , 8 , 19 , 20 , 21 ]. The lipid bilayer protects intra-vesicular RNA from extra-vesicular RNases, and proteins from extracellular proteases, thereby increasing the biological half-life of the intra-vesicular content [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation